Molecular markers for biomass burning associated with the characterization of PM 2.5 and component sources during dry season haze episodes in Upper South East Asia - Duangduean Thepnuan (2019)
© 2018 Severe air pollution in the form of smoke haze in the northern part of Southeast Asia (SEA) occurs annually in the dry season due to huge open area burning. Molecular markers of biomass burning were investigated by characterization of fine particles (PM 2.5 ) collected in the dry season (23 February–28 April 2016). The average PM 2.5 , organic carbon (OC) and elemental carbon (EC) concentrations were 64.3 ± 17.6 μg m −3 , 23.6 ± 8.1 μg m −3 and 2.85 ± 0.98 μg m −3 , respectively. SO 42− was the dominant species (8.73 ± 2.88 μg m −3 ) of water-soluble ion, followed by NH 4+ (3.32 ± 1.01 μg m −3 ) and NO 3− (2.70 ± 0.51 μg m −3 ). High concentrations of the biomass burning tracers K + (1.27 ± 0.38 μg m −3 ) and levoglucosan (1.22 ± 0.75 μg m −3 ) were observed. The ratios of levoglucosan/K + (0.92 ± 0.35) and levoglucosan/mannosan (20.4 ± 4.1) identified forest and agricultural waste burning as major contributors to the aerosol. Strong correlations (r > 0.800) between levoglucosan and OC, K + , anhydrosugar isomer (mannosan and galactosan) and other saccharides (mannose, arabitol and mannitol) verified that combustion of biomass was the major source of organic compounds associated with PM 2.5 aerosols. Oxalate was the most abundant (0.75 ± 0.17 μg m −3 ; 53%) of the carboxylates. The concentration of oxalate was strongly correlated to that of PM 2.5 (r = 0.799) and levoglucosan (r = 0.615), indicating that oxalate originates mainly from primary emissions from biomass burning rather than secondary formation from photochemical processes. Backward trajectories indicated that long-range transport air masses influencing air quality in Northern Thailand originated to the west and southwest.